The Role of Pre-ablative Stimulated Thyroglobulin and Thyroglobulin/Thyroid-Stimulating Hormone Ratio for Predicting Metastasis in Thyroid Cancer - Demir, Fadime; Simsek, Fikri Selcuk; Balci, Tansel Ansal (Galenos Publ House, 2019)
Objectives: In this study, we aimed to investigate the predictive value of pre-ablative stimulated thyroglobulin (Tg) and Tg/thyroid-stimulating hormone (TSH) to identify lymph node metastasis (LNM) or distant metastases (DM) prior to radioactive iodine (RAI) treatment. Methods: Patients without metastasis were included in group 1 (n=100), those with LNM were included in group 2 (n=83), and those with DM constituted group 3 (n=23). Tg and TSH values were measured approximately 4 hours prior to RAI ablation therapy. Results: There was a significant difference between group 3 and other groups (group 1 and group 2) in terms of Tg (p<0.001) and Tg/TSH (p<0.001). For Tg level and Tg/TSH ratio, the areas under ROC were 0.990 [95% confidence interval (CI): 0.979-1] and 0.991 (95% CI: 0.981-1), respectively. The cut-off points for Tg and Tg/TSH were 102 ng/mL and 1.06, respectively. Conclusion: Our results suggest that Tg and Tg/TSH values can be used to predict DM. On the other hand, our study indicates that patients should be carefully evaluated for LNM even when Tg levels are low.
Tiroid kanserinde pre-ablatif stimüle tiroglobulin ve tiroglobulin/tiroid uyarici hormon oraninin metastaz tahminindeki rolü
Keywords: Thyroid cancer; thyroglobulin; metastasis